Pengaruh Jarak Tanan dan Berbagai Jenis Mulsa Terhadap Pertumbuhan dan Produksi Tanaman Tomat (Lycopersicum Esculentum Mill) Varietas Servo F1 - Novan Budi S; Tarwa Mustopa (STAI Hidayatut Thullab Kediri, 2022)
ATomato (Lycopersicum esculentum Mill) is a popular fruit vegetable and has many important roles in fulfilling nutrition. Tomato (Lycopersicon esculentum Mill) is a type of vegetable that is very popular among the public. Tomato production in Indonesia in 2017 was 747,577 tons/year. In 2018 the production of tomato plants decreased to 707,601 tons/year. In 2019, tomato production increased to 995,636 tons/year. In 2020, tomato production will increase to 1,015,636 tons/year. To maintain this production, better cultivation techniques are needed. To increase tomato production, one of which is setting the spacing, which is also one of the commonly used cultivation techniques in order to obtain optimal spacing in terms of specific properties for different types of plants. To increase tomato production, apart from setting the spacing, the use of mulch, one of the efforts that can be done is to choose mulch as a good ground cover. Mulch plays a role in reducing the rate of evaporation of water and nutrients. This research will start from February 2021 to May 2021. Located in Uniska Land, Manisrenggo Village, Kota Kediri District, with an altitude of ± 100 meters above sea level, tropical climate with an average temperature of 28˚C and the type of sandy loam soil with a soil pH of 6 ,5. This study used a factorial randomized block design (RAK) with two factors. The first factor is the spacing with 3 levels symbolized (J) and the second factor is mulch with 3 levels symbolized (M) which was repeated 3 times with 27 treatment plots. The data obtained from the observations on each variable were entered into a table for the F test to be performed using the variance method (ANOVA). If there is a real or very real interaction from each treatment, the comparison test is carried out using DMRT Level 5% and BNT Level 5%. The results of this study showed that there was an interaction between the treatment of plant spacing and the type of mulch on the variable height of the plant when the age of observation was 21 Hst, namely J1M0 53.75 cm. In the single treatment plant spacing, there was a significant effect on the observation variable for the number of fruit (J3) 50 x 60 cm, namely 24.4 fruit and the fruit weight variable for planting (J3) 50 x 60 cm, which was 1016.70 g. While the single treatment of mulch type had a significant effect on the variable number of fruit (M1) black silver mulch which was 26.42 pieces and fruit weight per plant (M1) silver black mulch was 1164.43 g and fruit weight per plot (M1) silver black mulch 16.22 kg. When converted to hectares the most effective J2M1 53.77 tons.